Juridical Analysis Of The Authority Of Immigration Officers At Immigration Checkpoints In Granting Exit Permits For Indonesian Citizens As An Effort To Prevent Human Trafficking (A Research Study At The Batam Center Immigration Checkpoint) - Julyanty Dinauli Marisi Silitonga; Soerya Respationo; Siti Nurkhotijah; Erniyanti Erniyanti (Journal of Innovative and Creativity, 2025)
This study aims to analyse, from a legal perspective, the authority of immigration officers at Immigration Checkpoints (TPI) in granting exit permits to Indonesian citizens (WNI) to prevent the crime of human trafficking (TPPO). The focus of this research is on the implementation of the authority of immigration officers at Batam Centre TPI, one of Indonesia's main exit points and a region vulnerable to human trafficking. The research method used is a qualitative approach with field studies in the form of observation, interviews, and analysis of relevant legislative documents. The research results show that immigration officials' authority is regulated in Law Number 6 of 2011 concerning Immigration and Minister of Law and Human Rights Regulation Number 44 of 2015. Immigration officials have the right to postpone or deny exit permits if there are indications of human trafficking risks. This authority has been implemented through document checks, interviews, and the Immigration Management Information System (SIMKIM). However, there are still obstacles such as limited human resources, suboptimal information technology integration, and limited inter-agency coordination. This study recommends enhancing human resource capacity, developing and integrating better information technology systems, and strengthening coordination among relevant agencies to reinforce TIP prevention by issuing exit permits at TPI Batam Centre. Thus, it is hoped that immigration officials' authority can be effectively implemented to protect Indonesian citizens from the risks of human trafficking.